Analisis Pengaruh Komposisi Pegawai Dan Tarif Gaji Terhadap Belanja Pegawai - Ridwan, Achmad; Rosihana, Athiy Dina; Saputra, Wawan; Pratiwi, Cindya Yunita (AL-MIKRAJ Jurnal Studi Islam dan Humaniora, 2024)
The amount of employee expenditure burden in the State Budget (APBN) increases from year to year, the increase needs to be observed whether it is due to the rapid growth in the number of Civil Servants (PNS) or other causes such as recent government policies in terms of improving PNS income and welfare by adjusting PNS salary rates. This study aims to determine whether the increase in employee expenditure is more due to the increase in the number of PNS or PNS salary rates. The purpose of this study is to explain whether there is a significant influence between employee composition and salary rates on employee expenditure. This study is a quantitative study with statistical analysis. The data collection method used is through document and literature review methods, based on the source, the document is included in the secondary data category. The data testing method uses a normality test with the One-Sample Kolmogorov-Smirnov Test method. The data analysis method uses descriptive statistical analysis and hypothesis testing uses Multiple Linear Regression. Based on the results of the study with a significance level of 5%, the following conclusions were obtained: (1) There is a positive but insignificant influence between the number of PNS group I on employee expenditure; (2) There is a positive but insignificant influence between the number of PNS group II on employee expenditure; (3) There is a positive but not significant influence between the number of class III civil servants on employee expenditure; (4) There is a positive and significant influence between the number of class IV civil servants on employee expenditure; (5) There is a positive and significant influence between class I salary rates on employee expenditure; (6) There is a positive and significant influence between class II salary rates on employee expenditure; (7) There is a positive and significant influence between class III salary rates on employee expenditure; (8) There is a positive and significant influence between class IV salary rates on employee expenditure; (9) There is a positive but not significant influence between employee composition and salary rates; (10) There is a positive and significant influence on the number of class I civil servants, the number of class II civil servants, the number of class III civil servants, the number of class IV civil servants, class I salary rates, class II salary rates, class III salary rates and class IV salary rates together on employee expenditure.